Antifogging and ice-phobic wire with multi-level micro-nano-porous structure, preparation method and application in long-acting anti-condensation

CN122417534BActive Publication Date: 2026-11-03CHONGQING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610882832.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-18
Publication Date
2026-11-03
Estimated Expiration
2046-06-18

AI Technical Summary

Technical Problem

Existing multi-level micro-nanoporous wire structures have insufficient anti-condensation performance in low-temperature and high-humidity environments, making it difficult to meet the long-term anti-icing requirements of power transmission lines. Furthermore, the manufacturing process suffers from high costs and poor environmental performance.

Method used

A multi-level micro-nanoporous structure, including micron-pits, submicron-pits, and nanopores, was prepared on an aluminum substrate. By combining two anodic oxidation processes with oxalic acid electrolyte and modification agent treatment, the porosity and morphology were optimized to form a tertiary micro-nanoporous structure.

Benefits of technology

It achieves anti-condensation performance for up to 90-98 hours in low temperature and high humidity environments, has anti-icing function during the icing cycle, and has self-healing properties and durability, reducing manufacturing costs and environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122417534B_ABST
    Figure CN122417534B_ABST
Patent Text Reader

Abstract

The application belongs to the field of ice-preventing material preparation, and particularly relates to an ice-preventing and ice-repellent wire with a multi-stage micro-nanopore structure, a preparation method and application in long-acting anti-condensation. The application first provides an ice-preventing and ice-repellent wire with a multi-stage micro-nanopore structure, which is a multi-stage micro-nanopore structure formed on an aluminum base or an aluminum alloy base, and the multi-stage micro-nanopore structure is a structure containing sub-micropits and nanopores in micropits. It is verified through experiments that the long-acting ice-preventing and ice-repellent wire with a three-stage micro-nanopore structure provided by the application can maintain anti-condensation failure performance for 90-98 hours in a low-temperature and high-humidity environment, and has the potential to play an ice-preventing role within an icing period (3-4 days).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of anti-icing material preparation, specifically relating to an anti-icing wire with a multi-level micro-nanoporous structure, its preparation method, and its application in long-term anti-condensation. Background Technology

[0002] Icing disasters on transmission lines are one of the most serious threats to power systems. Compared with other types of power grid accidents, icing disasters cause more severe losses to the power grid. Although DC de-icing technology has effectively addressed the impact of icing disasters on the power grid, the manpower and material resources consumed during power outages for de-icing are enormous. The industry urgently needs to develop from "passive protection" de-icing technology to "active defense" conductor anti-icing technology. Currently, superhydrophobic surface technology has shown certain advantages in anti-icing effectiveness; however, its application still faces significant bottlenecks. For example, in low-temperature and high-humidity environments, water vapor easily condenses in ordinary superhydrophobic microstructures, leading to mechanical interlocking and rendering the anti-icing performance ineffective.

[0003] Previous studies have shown that hierarchical micro / nanoporous wire structures can increase the wetting transition energy barrier, causing frozen droplets to transition from a hydrophilic (Wenzel state) to a superhydrophobic (Cassie state), thus achieving long-term anti-condensation effects. However, the anti-icing or anti-condensation performance of these disclosed hierarchical structures still needs improvement; currently, there is a lack of systematic reports on the relationship between the specific hierarchical configuration, the size range of each level, and the anti-icing performance of disclosed micro / nanoporous wire structures. For example, authoritative journals in this field, *ACS Nano* and *Advanced Materials*, have conducted comparative reviews of the anti-condensation failure times of various hierarchical structures reported before 2025, finding that currently reported hierarchical structures designed and fabricated using laser etching, which is difficult to mass-produce, can achieve an anti-condensation effect of up to 33 hours. However, this anti-condensation effect is insufficient to meet the anti-icing requirements of power transmission lines for a natural icing period of 3-4 days (72-96 hours).

[0004] Currently, while domestic and international models for anti-icing and anti-wetting properties provide basic structural parameters for maintaining static and dynamic droplet wettability (CB state), the contact angle is still a crucial factor. θ The droplet volume is relatively macroscopic, ranging from 1 to 10 μL, with a droplet diameter of approximately 1240-2670 μm. However, in natural icing environments, the droplet size of rime and freezing rain ranges from 10 to 80 μm, much smaller than the droplet sizes reported in existing studies. Therefore, pore structure parameters obtained solely based on the superhydrophobic principle are insufficient to resist anti-icing failure caused by the condensation of microdroplets within the pore structure in real environments such as rime and freezing rain. Therefore, further development and optimization of pore structure designs to resist microdroplet condensation failure has significant academic value and practical engineering implications for anti-icing of conductors.

[0005] In summary, it is necessary to propose a novel multi-level porous structure design with a longer resistance to condensation failure for the fabrication of anti-icing wires to meet the application needs in this field. Summary of the Invention

[0006] The purpose of this invention is to provide an anti-icing wire with a multi-level micro-nanoporous structure, its preparation method, and its application in long-term anti-condensation, thereby partially solving or alleviating the above-mentioned deficiencies in the prior art. The specific technical solution adopted by this invention is as follows.

[0007] An anti-icing wire with a multi-level micro / nanoporous structure is disclosed. The wire is formed on an aluminum substrate or aluminum alloy substrate with a multi-level micro / nanoporous structure. The multi-level micro / nanoporous structure is a structure that simultaneously contains submicron pits and nanopores within micron pits. The width of the micron pits is less than or equal to 5 μm; the width of the submicron pits ranges from 0.5 to 1 μm; the width of the nanopores ranges from 50 to 300 nm; the porosity of the multi-level micro / nanoporous structure formed on the wire is 60%-70%, and the morphology of the multi-level micro / nanoporous structure is intact or substantially intact. The term "basically complete structure of multi-level micro-nanopores" means that the proportion of multi-level micro-nanopores with complete structure is at least greater than 60% among all multi-level micro-nanopores.

[0008] As a preferred embodiment, the structure of the multi-level micro-nanopores exhibits a near-circular or hexagonal shape.

[0009] As a preferred embodiment, the width of the micro-pit is in the range of 1-5 μm; the width of the submicron pit is in the range of 0.5-1 μm; and the width of the nanopore is less than 110 nm.

[0010] Preferably, the width of the nanopore is in the range of 100-110 nm. More preferably, the width of the nanopore is 100 nm.

[0011] As a preferred embodiment, the porosity of the multi-level micro / nanopore structure formed on the wire is 65%-70%.

[0012] Furthermore, the roughness Ra of the multi-level micro-nanoporous structure ranges from 1 to 2 μm; it is determined based on the standard "SO 4288 (1996) Surface Texture Evaluation Rules and Procedures".

[0013] As a preferred embodiment, a (-O-Si) modifier is bonded to the surface of the conductor substrate or a modifier is filled into the multi-level micro / nanopores of the conductor; the type of modifier includes fluorinated organosilicon compounds.

[0014] As a preferred embodiment, the modifier is 3-30 wt.% perfluorooctyltriethoxysilane.

[0015] The above-mentioned method for preparing anti-icing wires with multi-level micro / nanoporous structures includes the following steps: S01: Aluminum conductor surface pretreatment for cleaning; S02: Immerse the aluminum wire in oxalic acid electrolyte and perform two anodic oxidation treatments; The first anodizing process was set to a voltage-stabilized mode with a voltage of 50-60V and an oxidation time of 10-20 minutes. The second anodizing process was set to a current-stabilized mode with a current density of 0.01~0.50 A / cm². 2 The oxidation treatment time is 10-20 minutes; Controlling Fe in the electrolyte 3+ The concentration is no more than 1 g / L.

[0016] Furthermore, the concentration of oxalic acid in the oxalic acid electrolyte is set to 0.3-1.2 mol / L.

[0017] As a preferred option, the aluminum ion concentration in the oxalic acid electrolyte is set to 0.02-10 g / L (aluminum ion concentration is a necessary condition for the initial reaction; preparation can only proceed after this condition is met); alternatively, the Fe concentration in the electrolyte is controlled. 3+ The concentration is 0.2-1 g / L.

[0018] More preferably, controlling the Fe in the electrolyte 3+ The concentration is 0.2 g / L.

[0019] As a preferred option, the temperature of the oxalic acid electrolyte is set to 10-20℃.

[0020] As a preferred embodiment, the voltage regulation mode of the anodizing is set to a rapid boost mode.

[0021] As a preferred option, the regulated voltage for the first anodizing is 55V.

[0022] As a preferred embodiment, the steady-state current density for the second anodizing is 0.25 A / cm². 2 .

[0023] As a preferred option, the two anodizing cycles take 20 minutes each.

[0024] In some preferred embodiments, the SO2-treated wires are immersed in a finishing agent for infusion, followed by heat treatment.

[0025] The above-mentioned anti-icing wire with multi-level micro-nanoporous structure is used in the preparation of long-lasting anti-condensation equipment.

[0026] The above-mentioned anti-icing wire with multi-level micro-nanoporous structure is used in the preparation of durable anti-icing devices.

[0027] The present invention can also provide another technical solution.

[0028] A multi-level micro / nanoporous structure design with durable anti-icing properties is disclosed. The multi-level micro / nanoporous structure is a structure that simultaneously contains submicron pits and nanopores within micron pits. The width of the micron pits is less than or equal to 5 μm; the width of the submicron pits ranges from 0.5 to 1 μm; the width of the nanopores ranges from 50 to 300 nm; the porosity of the multi-level micro / nanoporous structure generated on the conductive wire is 60%-70%, and the structural morphology of the multi-level micro / nanoporous structure is basically intact.

[0029] Beneficial technical effects: This invention provides a long-lasting anti-icing wire with a three-level micro / nanoporous structure. This three-level micro / nanoporous structure is a composite structure containing nanoscale, submicron-scale, and micron-scale pores or pits, hence the name three-level micro / nanoporous structure. This three-level micro / nanoporous structure design enables droplets to maintain a stable Cassie state (superhydrophobic state) in low-temperature, high-humidity environments for extended periods, without deteriorating into a Wenzel state (hydrophilic state). Experimental verification shows that the long-lasting anti-icing wire with the three-level micro / nanoporous structure provided by this invention can maintain its anti-condensation failure performance for 90-98 hours in low-temperature, high-humidity environments, possessing the potential to provide anti-icing protection within one icing cycle (3-4 days). The wire with the three-level micro / nanoporous structure provided by this invention also exhibits durable anti-icing performance, maintaining low ice adhesion strength even after multiple icing / de-icing cycles, several days of thermal aging, UV radiation, mechanical wear, and corona aging, demonstrating good self-healing properties and effectively extending its durability.

[0030] In this invention, through simulation analysis of the impact and wetting behavior of simulated frost droplets on different micro / nano structures, based on the wetting transition model and phase interface dynamics equation, the influence of different micro / nano structure parameters on the thickness and duration of the superhydrophobic surface air cushion layer was studied and obtained. This led to the optimization of a multi-level micro / nanoporous structure for anti-icing, composed of nano-sized pores with high aspect ratio and narrow gaps, and micron-sized pits. The key geometric parameters are as follows: the gap ratio and aspect ratio of the first-level nanopores are greater than 9.50 and 1.08, respectively, and the pore size is less than 134.60 nm; the sizes of the second- and third-level micron-pits are in the ranges of 0.5–1 μm and 1–5 μm, respectively. This achieved anti-condensation failure performance for up to 98 and 90 hours under simulated laboratory and natural low-temperature, high-humidity icing environments, respectively.

[0031] To achieve the fabrication of the aforementioned anti-icing wire structure, this invention also provides a fabrication process: a secondary anodizing method combining a voltage-stabilized mode and a current-stabilized mode. In the first stage of the reaction, a high voltage is applied to cause breakdown of the initial oxide film at weak points, inducing the formation of numerous randomly distributed initial pits of varying sizes. In the second stage, a tertiary micro / nanoporous structure with a certain degree of undulation and a relatively uniform morphology is fabricated using a current-stabilized mode. Compared to existing technologies, the fabrication process of this invention offers advantages in simplicity, economy, and environmental friendliness.

[0032] 1) Conventional methods for preparing phosphate composite pores require high voltages (90-200 V), far exceeding the voltages required for preparing oxalic acid pores (50-60 V). In the domestic market, due to cost control considerations, most DC anodizing plant production lines are equipped with rectifiers whose maximum output voltage is limited to 60-80 V. To output voltages above 110 V, custom-made high-voltage rectifiers are required, which significantly increases equipment costs and energy consumption. Therefore, the preparation process of this invention is more economical and more suitable for market promotion.

[0033] 2) The present invention uses oxalic acid electrolyte, which greatly reduces the phosphorus-containing wastewater generated during the use of phosphoric acid electrolyte (which does not meet the requirements of GB 8978-1996 "Integrated Wastewater Discharge Standard"). The preparation process of the present invention is more environmentally friendly. Attached Figure Description

[0034] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. The elements or parts in the drawings are not necessarily drawn to scale. Obviously, the drawings described below are some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without any creative effort.

[0035] Figure 1 The figures show a comparison between the three-level micro / nanoporous structure designed in this invention and the reported multi-level structures (a) Simulation results of the Ref-multi-level structure under frost impact at room temperature; b) Simulation results of the Ref-multi-level structure under frost impact at low temperature; c) Simulation results of the three-level micro / nanoporous structure in this study under frost impact at room temperature; d) Simulation comparison results of the three-level micro / nanoporous structure in this study under frost impact at low temperature; e) Droplet height changes and comparisons of different structures at room temperature and low temperature; f) Air cushion thickness changes and comparisons of different structures at room temperature and low temperature. Figure 2 SEM images of the conductors after anodizing under different energizing modes (a is the voltage regulation mode, b is the current regulation mode). Figure 3 SEM images of the conductors after anodizing at different oxidation voltages; Figure 4 SEM images of the conductors after anodic oxidation at different oxidation times; Figure 5 The images show the morphology and three-dimensional roughness of the conductors after primary and secondary anodizing (a is primary anodizing, b is secondary anodizing). Figure 6 SEM microstructure images of wires after anodizing at different electrolyte temperatures (a: high temperature manufacturing, b: low temperature manufacturing). Figure 7 For different Fe 3+ Macroscopic and microscopic morphology of wires after anodic oxidation at different ion concentrations (a is high Fe) 3+ Ion concentration, b is low Fe 3+ (ion concentration); Figure 8 Model diagrams of pore structures of different orders were constructed for simulation; Figure 9 Simulation results of droplet impact behavior for pore structures of different orders are shown in the figure (a is a zero-order smooth plane, b is a first-order nanopore structure, c is a second-order submicron pit / nanopore structure, d is a third-order micron pit / nanopore structure, e is a fourth-order micron pit / nanopore structure). Figure 10 Statistical results of simulation of droplet impact behavior with different pore structures (a is the droplet height of different pore structures, b is the air cushion thickness of different pore structures). Figure 11 Simulation results of droplet impact behavior on a three-level micro / nanopore structure with micrometer-scale pits of different widths are shown in the figure (a is 12 μm wide, b is 8 μm wide, c is 4 μm wide, d is 1 μm wide, e is a comparison of droplet height variation with micrometer-scale pits of different widths, and f is a comparison of air cushion thickness variation with micrometer-scale pits of different widths). Figure 12 Simulation results of droplet impact behavior on a three-level micro / nanopore structure with micrometer-scale pits of different depths are shown in the figure (a is a depth of 1 μm, b is a depth of 3 μm, c is a depth of 5 μm, d is a comparison of droplet height changes in micrometer-scale pits of different depths, and e is a comparison of air cushion thickness changes in micrometer-scale pits of different depths). Figure 13 shows the simulation results of droplet impact behavior on a three-level micro / nanopore structure with submicron-sized pits of different widths (a is a width of 1 μm, b is a width of 0.75 μm, c is a width of 0.5 μm, d is a comparison of droplet height changes with submicron-sized pits of different widths, and e is a comparison of air cushion thickness changes with submicron-sized pits of different widths). Figure 14 Simulation results of droplet impact behavior on a three-level micro / nanopore structure with submicron-level pits at different depths are shown in the figure (a is a depth of 1 μm, b is a depth of 0.75 μm, c is a depth of 0.5 μm, d is a comparison of droplet height changes in submicron-level pits at different depths, and e is a comparison of air cushion thickness changes in submicron-level pits at different depths). Figure 15 Simulation study of droplet impact behavior on a third-order micro / nanopore structure with nanopores of different widths, and comparison results of air cushion thickness variation (a is...). D p The thickness of the air cushion is equal to 300nm, where b is... D p The measurement of the air cushion thickness is equal to 100nm. c represents the change and comparison of the air cushion thickness over time with different widths of nanopores, and d represents the change in air cushion thickness with different widths of nanopores. Figure 16 Figure shows the results of the study on the pore limit size and apparent contact angle of the pore structure under different droplet impact velocities; Figure 17 A schematic diagram illustrating the pinning process and mechanism of droplets in a superhydrophobic porous structure; Figure 18 The images show Cryo-FIB / SEM images of the phenomenon of a large number of droplets detaching during the cutting of droplets by the multi-level micro-nano porous wires of the present invention (a is before ion beam cutting of droplets, b is the detachment of multiple droplets, c is the droplet detachment area, and d is the droplet detachment area). Figure 19 The results show the variation of different superhydrophobic wires under simulated low temperature and high humidity conditions (a) shows the variation of ice adhesion strength with simulated icing time, and b) shows the variation of contact angle with simulated icing time. Figure 20 The results show the variation of different superhydrophobic conductors under natural low temperature and high humidity conditions (a) shows the variation of ice adhesion strength with outdoor icing time, and b) shows the variation of contact angle with outdoor icing time. Figure 21 Figures showing the anti-icing performance of different superhydrophobic conductors; Figure 22 Figure 1 shows the results of the anti-frost performance of different superhydrophobic conductors; Figure 23 The results show the durability comparison between the superhydrophobic conductor of the present invention and the composite hole conductor of the prior art (a is the ice adhesion strength under multiple icing and de-icing cycles, b is the ice adhesion strength after aging at 110°C for several days, c is the ice adhesion strength after UV irradiation for several days, d is the ice adhesion strength after salt spray aging for several days, e is the ice adhesion strength after multiple wear cycles, and f is the ice adhesion strength after corona aging for several hours). Detailed Implementation

[0036] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0037] In this document, "and / or" includes any and all combinations of one or more of the listed related items.

[0038] In this article, "multiple" means two or more, that is, it includes two, three, four, five, etc.

[0039] As used in this specification, the term "about" typically means + / -5% of the value, more typically + / -4% of the value, more typically + / -3% of the value, more typically + / -2% of the value, even more typically + / -1% of the value, and even more typically + / -0.5% of the value.

[0040] In this specification, certain embodiments may be disclosed in a range-bound format. It should be understood that this "range-bound" description is merely for convenience and brevity and should not be construed as a rigid limitation on the disclosed range. Therefore, the description of a range should be considered as having specifically disclosed all possible subranges and the individual numerical values ​​within those ranges. For example, a description of the range 1-6 should be considered as having specifically disclosed subranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and the individual numbers within those ranges, such as 1, 2, 3, 4, 5, and 6. This rule applies regardless of the breadth of the range.

[0041] Definition of the noun: The "low temperature and high humidity" environment described in this invention usually refers to an environment where low temperature and high water vapor content coexist, typically -20~0℃, with a relative humidity ≥80%. The "multi-level porous structure" described in this invention refers to a porous composite structure with different scale ranges or spatial levels; the different scales include nanoscale, submicron scale and micron scale.

[0042] The embodiments of the present invention provide hole structures with different spatial levels, including: The primary structure is fabricated using a constant current mode, with the current typically set to 0.01~1 A / cm. 2 The morphology is a flat and uniform nanoporous structure; The secondary structure is prepared by voltage regulation mode, with the voltage typically set to 20~60 V, and the morphology is a nanoporous structure with excessive fluctuations and unevenness. The three-stage structure is fabricated using a voltage and current stabilization mode, with the voltage typically set to 20~60 V and the current typically set to 0.01~1 A / cm. 2 The morphology is a relatively uniform, undulating, three-level nanoporous structure.

[0043] The “nanopore” mentioned in this invention refers to a pore structure with a nanoscale range (50~500 nm).

[0044] The “micron pit” mentioned in this invention refers to a pit structure with a micron scale range (>1 μm).

[0045] The "submicron pit" mentioned in this invention refers to a pit structure (0.5μm~1 μm) with a micron scale but smaller than the micron pit scale.

[0046] The "air cushion" described in this invention refers to an air film formed by air pockets trapped between the solid and liquid interfaces, which prevent liquid from wetting the grooves in the rough structure of the superhydrophobic surface, thus lifting water droplets to form a Cassie state.

[0047] Example 1 1. Simulation method for multi-level structural design A simulation method for the wetting behavior of impact microdroplets on micro / nanostructures was employed. Based on the wetting transition model and the Cahn-Hilliard equations of phase interface dynamics, the influence of different structural parameters on the thickness and duration of the superhydrophobic surface cushion layer was systematically studied, thereby determining the optimal parameters for a multi-level structure that combines anti-condensation and anti-icing properties under low-temperature and high-humidity conditions. This simulation method, based on the two-phase flow-phase field method of COMSOL Multiphysics 6.3, simulated the wetting behavior of impact microdroplets on different superhydrophobic structures.

[0048] Numerical simulations must adhere to fundamental conservation laws, and the core governing equations for droplet impact simulations are as follows. Considering the wetting energy and amount of wetted material in each element, a one-dimensional wetting transition model is used to establish the relationship between the substrate structure and the wetting state transition, as shown in the following equation. γ LA , γ SL as well as γ SA These represent the surface tensions at the liquid-gas, solid-liquid, and solid-gas interfaces, respectively. θ E The Young's contact angle represents the plane. The diameter of the pore structure is denoted as... a The width of the hole wall is recorded as b The wetting height of the pore structure is denoted ash Total wetting energy required E It can be modeled as Equation (3). The governing equations of droplet impact include the continuity equation, the momentum conservation equation, and the Cahn-Hilliard equation (evolution of phase interface dynamics). Among them, the fluid is incompressible and the velocity gradient is 0. In Equation (5), F is the applied external force; ρg It is a volume force, gravity; v For the velocity field (m / s); pI Pressure (Pa); I It is the identity matrix; μ( v+v r ) The term represents viscous stress; G φ The term originates from the chemical potential gradient introduced by the phase field, characterizing the surface tension effect. In formula (6), β The mobility (m) that determines the diffusion time of the Cahn-Hilliard diffusion is 3 s kg -1 ); It refers to the dimensionless phase field gradient.

[0049] (1); (2); (3); (4); (5); (6).

[0050] In the geometric parameter settings, the droplet diameters are 500 nm and 10 μm, corresponding to the minimum diameters of condensed droplets and icy droplets under low-temperature and high-humidity conditions, respectively. The impact velocity of the droplets is selected as the impact wind speed of a typical atmospheric icing condition, which is 3 m / s. The ambient temperatures are set to -5 ℃ and 20 ℃. The computational domain is 30 × 20 μm. The micro / nano structure parameters include a film thickness of 5 μm, nanoscale pore diameters of 50-300 nm, submicron-scale pit length and depth of 0.5-1 μm, and micron-scale pit length and depth of 1-5 μm. In addition, the droplet center position and contact angle in the geometric model satisfy specific constraints, and the contact angle of the structure's wetting wall is set to 150°. The following reasonable assumptions are introduced in the modeling process to simplify the model and improve computational efficiency: i) the droplet is spherical before contact; ii) the viscosity and surface tension of the fluid are considered constant during the droplet impact; iii) phase change and heat transfer effects at the gas-liquid interface are ignored.

[0051] 2. Laboratory preparation methods for micro / nanoporous structures Currently, most researchers employ the steady-current energizing mode of anodic oxidation, which can achieve the fabrication of traditional smooth, single-level nanoporous structures. When fabricating multi-level nanoporous structures on alumina through anodic oxidation, the choice of energizing mode (steady current or steady voltage) affects the balance of oxidation and dissolution kinetics, thus influencing the final pore structure morphology. The commonly used steady-current energizing mode maintains a constant current density, allowing the oxide film to grow slowly under a controllable, continuously increasing voltage. This condition promotes stable passivation kinetics, orderly nucleation and longitudinal growth of the oxide film, thus facilitating the formation of smooth, uniformly sized, and regularly arranged single-level nanoporous structures. However, while the steady-current energizing mode of anodic oxidation can produce uniform single-level pore structures, it presents a significant challenge for fabricating non-uniform, irregularly arranged multi-level nanopores.

[0052] Preferably, this invention employs a voltage-controlled anodic oxidation mode to prepare a hierarchical nanoporous structure with higher specific surface area and roughness. In the first stage of the reaction, this mode applies a high voltage to cause breakdown of the initial oxide film at weak points, inducing a large number of randomly distributed initial pits of varying sizes. In the second stage, a tertiary micro / nanoporous structure with a relatively uniform morphology and some undulations is prepared using a constant current mode.

[0053] This embodiment illustrates a laboratory method for fabricating a specific multi-level micro / nanoporous wire structure, including anodizing and post-modification treatments.

[0054] Experimental methods: 1) Surface pretreatment: Immerse the aluminum wire in sodium hydroxide solution for 10 minutes to remove surface grease and natural oxide film.

[0055] 2) Anodizing treatment: After pretreating the surface of the aluminum wire, two ends are connected to a 5×30 cm diameter graphite plate ring electrode. One end of the ring electrode serves as the cathode, and one side of the oxidation tank serves as the anode. The cathode and anode are connected to the negative and positive terminals of a DC output power supply, respectively. A two-stage anodizing process is used to prepare the hierarchical nanoporous structure. The first anodizing is performed in a voltage-stabilized mode with a voltage current of 20-60V, preferably 50-60V, and an oxidation time of 10-30 min, preferably 10-20 min. The second anodizing is performed in a current-stabilized mode with a current density of 0.01~0.50 A / cm². 2 Preferably, it is 0.2-0.3 A / cm. 2 The oxidation time is 10-30 min, preferably 10-20 min. The electrolyte is oxalic acid electrolyte with a concentration of 0.3-1.2 mol / L, a temperature of 5-40 ℃, preferably 10-20 ℃, and an aluminum ion concentration of 0.02-10 g / L and an iron ion concentration of 0.2-1 g / L.

[0056] 3) Post-modification treatment: After anodizing, the dried wire samples are immersed in 3-30 wt.% perfluorooctyltriethoxysilane (FAS) modifier and poured into a vacuum drying oven under negative pressure (-0.1 MPa, 3-12 h). Subsequent heat treatment (90-120℃, 1-12 h) promotes the formation of a stable molecular cross-linking layer on the surface of the modifier molecules, enhancing the cross-linking strength and durability between the modifier and the surface. This ultimately forms a multi-level porous wire.

[0057] 3. Performance Comparison 3.1 The performance parameters of the three-level micro / nanoporous structure of the present invention are compared with the performance parameters disclosed in prior art 1 and prior art 2. Prior art 1: Dual-Energy-Barrier Stable Superhydrophobic Structures for Long Icing Delay (WANG L, ZHONG M, ACS Nano, 2024, 18(19):12489-502); Prior art 2: CN116206801B.

[0058] 3.1.1 Simulation calculation of air cushion thickness The air cushion thickness data was obtained through simulation using the wetting module of Comsol software. The software simulated the droplet impact motion behavior and extracted the distance from the droplet to the structure as the air cushion thickness, thus obtaining the relationship between the air cushion thickness and time. To achieve effective anti-icing, the ability of the superhydrophobic structure's air cushion layer to continuously deflect droplets or maintain a Cassie-Baxter (CB) wetted state under long-term icing conditions is a crucial evaluation indicator. Therefore, air cushion thickness is a key parameter for evaluating the anti-icing performance of superhydrophobic structures; the thicker the air cushion, the better the anti-icing performance.

[0059] The thickness of the air cushion in the three-level micro / nanoporous structure prepared by this invention is compared with that of existing technologies. For example... Figure 1 As shown, the hierarchical micro / nanoporous structure prepared by this invention is compared with the Ref-level structure reported in prior art 1. The air cushion thickness of the prior art at room temperature (20℃) and low temperature (-5℃) is 0.9189 μm and 0.9127 μm, respectively. In contrast, the hierarchical micro / nanoporous structure of this invention can achieve air cushion thicknesses of 4.093 μm and 4.0509 μm at room temperature (20℃) and low temperature (-5℃), respectively, which are 4.454 and 4.438 times that of the most advanced research to date.

[0060] The three-level micro / nanopore structure of the present invention is then compared with the nanopore structure disclosed in prior art 2. At low temperature (-5°C), the air cushion thickness of the three-level micro / nanopore structure of the present invention is 4.051 μm, while the air cushion thickness of the nanopore in prior art 2 is 0.70 μm.

[0061] 3.1.2 Laboratory verification of anti-condensation time Anti-condensation time data were obtained by placing conductor samples in an icing test chamber and under natural conditions. The icing test chamber was customized based on IEC 60060-1 and ISO 12494:2017 structural atmospheric icing test standards, simulating low-temperature and high-humidity environmental conditions (-5℃, 99% RH); the low-temperature and high-humidity icing environment conditions under natural conditions were recorded as (-10~-4℃, 99% RH). The ice adhesion strength and hydrophobicity of the conductor samples were tested, and the failure time point was determined when the ice adhesion strength was greater than 20 kPa or the contact angle was less than 150°.

[0062] The hierarchical micro / nanoporous structure prepared by this invention can achieve an anti-condensation failure time of 90-98 hours in laboratory and natural low-temperature and high-humidity environments, which is nearly three times the longest reported delayed condensation time of 33 hours, and can significantly extend the anti-condensation time. Therefore, the hierarchical micro / nanoporous structure wire and its anti-icing device provided by this invention have the potential to play an anti-icing role within one icing cycle (3 days).

[0063] 3.2 Influence of preparation process on micro / nanoporous structure 3.2.1 Impact of Power-On Mode This embodiment employs anodized voltage regulation modes including segmented boost and rapid boost. The segmented boost mode maintains the voltage in stages at a certain boost rate and slowly increases it to the target voltage value. Figure 2 The microstructure of layer a shows that the oxide film prepared under the segmented voltage ramp mode is dense and has very few pores. This mainly slows down the electrolyte dissolution and etching process and promotes the growth of the barrier layer. Preferably, the rapid voltage ramp mode rapidly increases the voltage to the target value. The micro / nanopore structure prepared under this mode has a higher porosity. In this embodiment, the porosity of the nanopores prepared is 65.3%. Therefore, the rapid voltage ramp mode under the regulated voltage mode is preferred in subsequent analyses. In contrast, the commonly used current-stabilized mode, when not properly controlled, can result in high current values ​​applied to the orifice structure, leading to structural collapse, or even ablation of the aluminum strands and steel core. Figure 2 b). Observation of the unablated area in the steady current mode showed that the overall morphology was relatively flat, and its porosity (53.1%) was lower than that in the voltage stabilization mode (65.3%), indicating that the current was uneven due to ablation.

[0064] 3.2.2 Effect of Oxidation Voltage The morphology of wires prepared by different oxidation voltages is as follows Figure 3 As shown, the pore size gradually increases with increasing oxidation voltage. Figure 3 When the voltage is set to 50V, 52V, and 55V (from left to right), the porosity and pore size of the nanopores are 42.2% / 70nm, 56.3% / 80nm, and 68.1% / 90nm, respectively. As the voltage gradually increases to 58V, 60V, and 65V, the porosity and pore size of the nanopores are 73.1% / 100nm, 70.6% / 100nm, and 64.8% / 120nm, respectively. It can be seen that the porosity of the structure is highest when the voltage range is 55-60V, between 68.1% and 73.1%. However, as the voltage increases to 65V, the porosity decreases (to 64.8%). This is mainly because the pore structure overgrows under excessively high voltage, and the compression of adjacent pore walls causes partial damage to the structure, leading to a decrease in overall porosity. Therefore, an oxidation voltage range of 55-60V is preferred to achieve the preparation of micro / nanoporous structures with high porosity.

[0065] 3.2.3 Effect of oxidation time The morphology of wires prepared by different anodizing times is as follows: Figure 4As shown, oxidation times were set to 10 min, 20 min, 30 min, and 40 min from left to right. When the oxidation time was 10 min, the nanopore porosity was 59.8%; when the oxidation time was 20 min, the porosity increased to 65.8%, and the pore morphology changed from circular to hexagonal. As the oxidation time was further extended to 30 min, overgrowth occurred in the pore structure, leading to partial structural collapse. When the oxidation time was 40 min, ablation was observed on the surface of the wire. Therefore, an oxidation time of approximately 20 min is preferred.

[0066] 3.2.4 Effect of Anodizing Times The morphologies of the wires prepared by primary anodizing and secondary anodizing are as follows: Figure 5 As shown. Figure 5 The surface of the conductor after primary anodizing is uneven, exhibiting both hierarchical and multi-hierarchical pore structures at different sampling locations, with some areas showing very low porosity. Furthermore, the cross-sectional pore structure shows a relatively disordered, radiating pattern. Specifically, measurements were taken at three points on the primary anodized conductor, with thicknesses of 4.8 μm, 16.3 μm, and 31.8 μm, and surface roughness (Ra) of 0.38 μm, 0.67 μm, and 1.17 μm, respectively.

[0067] The conductive wires prepared by secondary anodizing exhibited overall consistency and uniformity in macroscopic morphology. Measurements were taken at three points on the secondary anodized conductive wire, revealing thicknesses of 27.2 μm, 25.3 μm, and 26.5 μm, respectively; and surface roughness (Ra) of 1.42 μm, 1.31 μm, and 1.36 μm, respectively. Furthermore, high-porosity hierarchical micro / nanopore structures were observed in all regions of the secondary anodized conductive wires, including micron-sized deep pits, micron-sized shallow pits, and nanopores.

[0068] 3.2.5 Effect of electrolyte temperature The electrolyte temperature is controlled by adjusting the power of the chiller. The morphologies of the wires prepared at different electrolyte temperatures are shown below. Figure 6 As shown. Figure 6 a represents a high temperature of 30-40℃; Figure 6 b represents a low temperature of 10-20℃. At higher temperatures, flocculent material appears to cover the surface of the porous structure. This may be due to the dissolution, hydrolysis, and precipitation of the upper surface porous structure, which then continues to grow and completely cover the porous structure. At lower temperatures, the anodic oxidation growth and dissolution reactions are in a relatively balanced state, forming a micro / nanoporous structure with high porosity.

[0069] 3.2.6 Effect of electrolyte ion concentration Different Fe 3+ The morphology of the wires prepared by concentration is as follows Figure 7 As shown (Fe) 3+ (Mainly originates from the dissolution within the aluminum stranded wire). Figure 7 In a, when Fe 3+ When the concentration exceeds 1 g / L, the aluminum stranded wire exhibits external burning and internal porous structure dissolution. Furthermore, the micro-galvanic corrosion formed by Fe and the Al matrix further promotes the ablation process. In contrast, Figure 7 In b, when Fe 3+ When the concentration is less than 0.2 g / L, the oxide film formed on the surface of the aluminum stranded wire is relatively uniform, and there is no ablation phenomenon. The internal pore structure is not destroyed, and the porosity is 62.7%.

[0070] Based on the preferred preparation process described above, this invention preferably uses the rapid voltage boost mode within the voltage stabilization mode, with an oxidation voltage of 55-60 V, an oxidation time of 20 min, and an oxalic acid electrolyte temperature set to 10-20 °C, while controlling the Fe... 3+ The concentration is 0.2 g / L.

[0071] Example 2 1. Multi-level micro / nano structure pore design like Figure 8 The following different multi-level structures were constructed through simulation: Level 0 (blank), Level 1 (nanopore), Level 2 (nanopore + submicron pit), Level 3 (nanopore + submicron pit + micron pit), Level 4 (nanopore + submicron pit + micron pit + stepped micron pit).

[0072] The wetting behavior of impacting droplets on different superhydrophobic structures was simulated using the two-phase flow-phase field method in COMSOL Multiphysics 6.3. In the geometric parameter settings, the droplet diameter was set to 500 nm and 10 μm, corresponding to the minimum diameter of condensed droplets under low-temperature and high-humidity conditions and the minimum diameter of droplets under rime icing conditions, respectively. The impacting droplet velocity was selected as the impact wind speed of 3 m / s under typical atmospheric icing conditions. The ambient temperatures were set to -5 ℃ and 20 ℃. The computational domain was 30 × 20 μm.

[0073] The micro / nano structure parameters include a film thickness of 5 μm, the droplet center position and contact angle in the geometric model satisfying specific constraints, and the contact angle of the structure's wetting wall being set to 150°.

[0074] Level 1: The diameter of the nano-pores is set to 50-300 nm, and the ratio of pore depth to pore width is set to 10 (calculated based on SEM microscopic results).

[0075] Secondary stage: The diameter of the nanoscale pores is set to 50-300 nm, and the ratio of pore depth to pore width is set to 10. Submicron-level pits are introduced, with their length and depth set to 0.5-1 μm.

[0076] Level 3: Nanoscale pores are set with diameters of 50-300 nm and a depth-to-width ratio of 10. Submicron pits are set with lengths and depths of 0.5-1 μm. Micron-scale pits are introduced with lengths and depths of 1-5 μm.

[0077] Level 4: Nanoscale pore diameter is set to 50-300 nm, and the depth-to-width ratio is set to 10. Submicron pit length and depth are set to 0.5-1 μm. Micron-scale pit length and depth are set to 1-5 μm. Additional micron-scale pits are introduced on top of the micron-scale pits to form a spatial-scale stepped structure, with a length and depth set to 1-5 μm.

[0078] like Figure 9 and Figure 10 As shown in Table 1, simulation studies were conducted on structures of different levels to determine the air cushion thickness parameters for each structure. Compared with the level 0 structure, the air cushion thickness of the first and second level structures increased slightly; the air cushion thickness of the third level structure increased significantly; and the air cushion thickness of the fourth level structure decreased compared to the third level, indicating that the third-level porous structure has the best hydrophobic stability.

[0079] Table 1. Cushion thickness of nanopores with different hierarchical structures 2. Based on the three-level micro / nanopore structure, the size of micron-holes, submicron-holes, and nanopores were optimized respectively. The width and depth of the 2.1 micrometer pit are designed as follows (Table 2). See results Figure 11 While keeping the nanopore size and submicron pit size constant, the smaller the width of the micron pit, the more significant the increase in the thickness of the air cushion.

[0080] See results Figure 12 While keeping the nanopore size and submicron pit size constant, varying the depth of the micron pit resulted in a maximum difference of only 0.98% in the thickness of the air cushion. Therefore, the depth variation had a relatively small impact on the droplet impact behavior.

[0081] Table 2 Micrometer-sized pits 2.2 The width and depth of the submicron pits are designed as follows (Table 3). See results Figure 13 While keeping the nanopore size and micro-pit size constant, the smaller the width of the submicron pit, the greater its air cushion thickness. Figure 14 The depth has a slight effect on the thickness of the air cushion. Therefore, adjusting the width and depth of the submicron pit has a small effect on increasing the thickness of the air cushion (only 0.37%).

[0082] Table 3 Submicron pits 3. The structural parameters of the nanopores are designed as follows: The pore size design of nanopores is crucial for improving the resistance to condensation and droplet pinning in low-temperature and high-humidity environments.

[0083] 3.1 Anti-condensation failure A simulation study was conducted using a superhydrophobic structure to achieve a minimum droplet diameter of 500 nm in a low-temperature, high-humidity environment, with operating wind speed parameters (3 m / s). The diameter of the anodic oxide pores ranged from 50 to 300 nm. See [link / reference]. Figure 15 (in, D p The diameter of the nanopore channel, D int The distance between the ribs of the nanopores. L For nanopore depth, k (where m is the gap ratio and m is the aspect ratio). Compared with the phosphate composite pore (300 nm), the small pore structure maintains the air cushion more effectively in a condensation environment. The preferred pore size range is 100 nm.

[0084] Table 4 Nanopores 3.2 Dynamic wettability: Contact angle / roll-off angle CAH / SA < 10° The minimum tilt angle at which a droplet begins to roll or slide when a solid surface is slowly tilted is called the roll angle (SA), which characterizes the rolling performance of the droplet. The difference between the forward contact angle and the backward contact angle of the droplet is the contact angle of dynamic wettability (CAH). The smaller the CAH angle, the easier it is for the droplet to roll and the more stable its hydrophobicity.

[0085] Dynamic wettability studies based on roll-off angle / contact angle hysteresis (SA / CAH) can further optimize structural parameter dimensions. Roll-off angle ( The reduction in the adhesion strength of water droplets to the surface directly reflects the decrease in the adhesion strength of water droplets on the superhydrophobic surface. τ as The roll-off angle can be obtained from the formula. When the surface has superhydrophobic properties, its roll-off angle is... <10°, after calculation, the solid-liquid contact area fraction fs<0.05, and the gap ratio k of the hexagonal pore structure>9.5.

[0086] (9); (10); (11).

[0087] 3.3 Resistance to droplet wetting Overhead power lines experience high wind speeds (3 m / s~5 m / s) during icing periods. This causes even tiny droplets impacting the structure under natural icing conditions to pin (penetrate and puncture) nanoscale structures. Therefore, the pore size needs further design to improve its resistance to penetration and puncture. Limiting the penetration and puncture of impacting droplets into the structure can be achieved by increasing the structure's resistance to wetting pressure (water shock wave pressure P). D +Bernoulli pressure P WH The structural parameters are optimized using interfacial energy (ΔG) and interfacial energy (ΔG). See Figure 16 By using a series of equations, a pore size below 116.6~134.6 nm was determined to achieve hydrophobicity and prevent failure due to puncture by impact droplets. The series of equations are as follows: Non-wetting pressure (resistance) includes capillary pressure, and the formula is: ; Where θA is the apparent contact angle; γLA is the surface energy of water at the water-vapor interface; and ∧ is the periodic void size of the structure. Wetting pressure (dynamic force) includes water shock wave pressure and Bernoulli pressure, as shown in the formula: ; Where c is the speed of sound in water; ρ and v correspond to the density and velocity of the droplet.

[0088] 3.4 Resistance to droplet puncture Even after a droplet penetrates the porous structure, it may continue to penetrate or retract. This study is based on interfacial energy (…). ΔG The theory continues to design structures to counteract droplet-perforated structures. The interfacial energy of the droplet's penetrating state must be less than the interfacial energy of its surface contact state. ΔG When <0, the smaller the aperture size (corresponding to a larger size), the better. γ L A L -γ L A’ L The better the hydrophobicity of the pore structure, the better. θ The larger the value, the more negative the interface energy. ΔG This demonstrates the inhibitory effect of the pore structure on droplet puncture. Figure 17 ).

[0089] (12); (13); (14); (15).

[0090] 4. Conclusion In summary, the parameters of the three-level micro / nanopore structure of this invention are determined as follows: the size ranges of the micron-pits and submicron-pits are 1~5 μm and 0.5~1 μm, respectively; the porosity P is 65%-70%; and the nanopore size D... p <116.6~134.6 nm, preferably less than 110 nm, and most preferably 100 nm.

[0091] Example 3 Experimental preparation and performance testing The three-level micro-nanopores were prepared according to the preferred schemes of Examples 1 and 2. The preparation steps are as follows. It should be noted that the following preparation method is only a specific example and should not be construed as a limitation of the present invention.

[0092] 1) Surface pretreatment: Immerse the aluminum wire in sodium hydroxide solution for 10 minutes to remove surface grease and natural oxide film.

[0093] 2) Anodizing treatment: After pretreating the surface of the aluminum wire, connect graphite plate (5×30 cm) ring electrodes with a diameter of 30 cm to both ends; one end of the ring electrode serves as the cathode, and one side of the oxidation tank serves as the anode. Connect the cathode and anode to the negative and positive terminals of the DC output power supply, respectively. Use two anodizing processes and oxalic acid electrolyte to prepare a multi-level nanoporous structure.

[0094] The first anodizing was performed in a voltage-stabilized mode with a voltage of 55V and an oxidation time of 20 minutes. The second anodizing was performed in a current-stabilized mode with a current density of 0.25 A / cm². 2 Oxidation time: 20 min. Oxalic acid electrolyte temperature: 10-20 °C, controlling Fe... 3+ The concentration is 0.2 g / L.

[0095] 3) Post-modification treatment: After anodizing, the dried wire samples are immersed in 3-30 wt.% perfluorooctyltriethoxysilane (FAS) modifier and poured into a vacuum drying oven under negative pressure (-0.1 MPa, 3-12 h). Subsequent heat treatment (90-120℃, 1-12 h) promotes the formation of a stable molecular cross-linking layer on the surface of the modifier molecules, enhancing the cross-linking strength and durability between the modifier and the surface. This ultimately forms a multi-level porous wire.

[0096] The prepared wire was verified by a freezing droplet experiment.

[0097] Methods: The condensation and frosting process of the micro / nanoporous structure on the wire surface and the contact state of the condensed droplets were observed using a cryo-ion / electron dual-beam electron microscope (FEI Aquilos Cryo-FIB / SEM, Thermo Fisher Scientific). First, the sample was placed on a cooling platform (-5±0.5 ℃, 90±2 %RH) for 0–2 hours for condensation and frosting treatment. Then, the sample was rapidly transferred to a liquid nitrogen environment (-190±5 ℃) for instantaneous freezing to lock in the wetting state of the condensed droplets. The sample was then transferred to the cryo-electron microscope chamber for in-situ metal deposition and ion beam cutting. A 20±2 nm thick Pt protective layer was sputtered at a 30° incident angle in FIB mode. The sample stage was then tilted to 52±1°, and the target droplet region was ion-beam cut using a 5 kV accelerating voltage. The morphology of the cut cross-section and the frozen morphology of the micro / nanostructure and the three-phase contact line of the droplet were observed and acquired.

[0098] See results Figure 18 When the interface bonding state was observed by cross-section cutting of the frozen droplets (dash circle area) of the hierarchical porous structure, many frozen droplets around it were found to automatically fall off, leaving multiple pits (multiple arrows), which proved that the hierarchical porous structure has extremely low ice adhesion strength.

[0099] The prepared wires were tested in a simulated low-temperature and high-humidity environment. Methods: The condensation and frosting behavior of droplets of hundreds of micrometers in size on the micro-nanoporous structure of the conductor surface was observed in situ using environmental scanning electron microscopy (Quattro S, Thermo Fisher Scientific). The vacuum level of the chamber was 10–4000 Pa, the beam current was 1 pA–200 nA, and the accelerating voltage was 200 V–30 kV. The sample was mounted on a brass sample holder, and the temperature of the sample stage was controlled within the range of -25–10 °C using a water-cooling system. The pressure inside the chamber was adjusted within the range of 150–900 Pa using vapor pressure. The condensation process of the sample inside the chamber was as follows: the environmental conditions inside the chamber were controlled at 2–3 °C and 800 Pa for 5 minutes to achieve a humidity of 100.0 RH%, and the pressure was gradually reduced to 500–550 Pa to reach the three-phase equilibrium position of water. The temperature was then lowered to -3–-5 °C to meet the low-temperature and high-humidity condensation conditions. To prevent the electron beam heating effect, the dynamic condensation process of a 2 cm aluminum monofilament sample was observed in real time using electron beam energies of 20 keV and 0.16 nA, respectively.

[0100] Meanwhile, commercially available aluminum stranded wire coated with a coating (DSAN-S2001-DL (III) type superhydrophobic wire anti-icing coating, patent CN109181537A, prepared by the manufacturer's recommended spraying method, the coating is composed of silica nanoparticles with a particle size of 20-100nm) and aluminum stranded wire with the primary pore structure in Example 2 were used as comparisons.

[0101] See results Figure 19 Commercially coated wires failed after 20 hours and exhibited hydrophilicity (21.1° and 212 kPa); single-level porous wires failed after 76 hours (149° and 21.4 kPa); and multi-level porous wires had the longest anti-condensation failure time, losing their anti-icing properties after 98 hours (20.3 kPa, 145°), demonstrating that multi-level micro-nano porous structures have excellent hydrophobicity and anti-icing properties.

[0102] like Figure 20 Under natural low temperature and high humidity conditions, the multi-level porous structure conductor can maintain low ice adhesion strength (<20 kPa) and superhydrophobic properties (CA>150°) for about 90 hours during atmospheric icing. The anti-icing conductor prepared by this invention has the potential to play an anti-icing role within one icing cycle (3 days).

[0103] like Figure 21 Both the commercially coated and anodized porous anti-icing wires exhibited superhydrophobic properties (CA>150°). In comparison, the hierarchical porous wire demonstrated the best hydrophobicity (CA=167°) and the lowest ice adhesion strength (2.8 kPa), which was only 1.3% of that of the blank wire. Figure 22 The 3-hour icing test showed that the icing weight of the multi-hole structure conductor was as low as 9.6g, which was 85.4% lower than that of the blank conductor (62.8g).

[0104] Example 4 Durability verification of anti-icing wires Conductor preparation steps: The three-level micro-nanopores were prepared according to the preferred schemes of Examples 1 and 2. The preparation steps are as follows. It should be noted that the following preparation method is only a specific example and should not be construed as a limitation of the present invention.

[0105] 1) Surface pretreatment: Immerse the aluminum wire in sodium hydroxide solution for 10 minutes to remove surface grease and natural oxide film.

[0106] 2) Anodizing treatment: After pretreating the surface of the aluminum wire, connect graphite plate (5×30 cm) ring electrodes with a diameter of 30 cm to both ends; one end of the ring electrode serves as the cathode, and one side of the oxidation tank serves as the anode. Connect the cathode and anode to the negative and positive terminals of the DC output power supply, respectively. Use two anodizing processes and oxalic acid electrolyte to prepare a multi-level nanoporous structure.

[0107] The first anodizing was performed in a voltage-stabilized mode with a voltage of 55V and an oxidation time of 20 minutes. The second anodizing was performed in a current-stabilized mode with a current density of 0.25 A / cm². 2 Oxidation time: 20 min. Oxalic acid electrolyte temperature: 10-20 °C, controlling Fe... 3+ The concentration is 0.2 g / L.

[0108] 3) Post-modification treatment: After anodizing, the dried wire samples are immersed in 3-30 wt.% perfluorooctyltriethoxysilane (FAS) modifier and poured into a vacuum drying oven under negative pressure (-0.1 MPa, 3-12 h). Subsequent heat treatment (90-120℃, 1-12 h) promotes the formation of a stable molecular cross-linking layer on the surface of the modifier molecules, enhancing the cross-linking strength and durability between the modifier and the surface. This ultimately forms a multi-level porous wire.

[0109] Since existing technology 1 can only be constructed on flat plates, it cannot be mass-produced on power transmission lines. Therefore, this patent verifies its superiority by comparing its durability with that of existing technology 2, which uses phosphate composite porous anodized wires.

[0110] Factors affecting the durability of conductor anti-icing include icing / de-icing cycle damage, heat, ultraviolet radiation, salt spray, mechanical abrasion, and corona aging. The test was conducted according to CIGRE-TB 631 "Protective Coatings for Overhead Power Grid Equipment under Winter Conditions" and CIGRE-TB 838 "Protective Coatings for Protecting Overhead Power Grids from Icing, Corona Noise, Corrosion, and Reducing Their Visual Impact." Results are shown in […]. Figure 23 .

[0111] The results showed that in the icing / de-icing cycle ( Figure 23 a) The cycle life of the multi-hole conductor (220 cycles) increased by 83.3% compared to the composite-hole conductor (120 cycles). In the environmental factor-induced thermal aging at 110 °C (… Figure 23 (b) The ice adhesion strength (11.3 kPa) of the multi-hole wire after 300 days of aging was 30.2% higher than that of the composite-hole wire (16.2 kPa); in the UV aging under environmental factors ( Figure 23c) The ice adhesion strength (14.7 kPa) of the multi-hole wire after 360 days of aging was 24.6% higher than that of the composite-hole wire (19.5 kPa); in the salt spray aging under environmental factors ( Figure 23 d) The ice adhesion strength of the multi-hole wire after 60 days of aging (13.9 kPa) was 15.2% higher than that of the composite-hole wire (16.4 kPa); in mechanical wear ( Figure 23 e) The multi-hole wire exhibits a 27.3% improvement in cycle resistance (140 cycles) compared to the composite-hole wire (110 cycles); in corona aging ( Figure 23 f) The corona resistance time of the multi-hole conductor (342 h) is 36.8% higher than that of the composite hole conductor (250 h).

[0112] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.

[0113] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims. All of these forms are within the protection scope of the present invention.

Claims

1. An anti-icing wire with a multi-level micro / nanoporous structure, characterized in that, The conductor is formed by generating a multi-level micro / nanopore structure on aluminum stranded wire. The multi-level micro / nanopore structure is a tertiary structure that simultaneously contains submicron pits and nanopores within micron pits. The width and depth of the micron pits are both 1-5 μm; the width and depth of the submicron pits are both 0.5-1 μm; the diameter of the nanopores is 100-110 nm; the porosity of the multi-level micro / nanopore structure generated on the conductor is 65%-70%, and the structure of the multi-level micro / nanopores exhibits a near-circular or hexagonal shape, with a complete morphology.

2. The anti-icing wire with a multi-level micro / nanoporous structure as described in claim 1, characterized in that, The roughness Ra of the multi-level micro / nanoporous structure ranges from 1 to 2 μm.

3. The anti-icing wire with a multi-level micro / nanoporous structure as described in claim 1, characterized in that, A modifier is bonded to the surface of the aluminum stranded wire or filled into the multi-level micro / nanopores of the aluminum stranded wire; the type of modifier includes fluorinated organosilicon compounds.

4. The method for preparing the anti-icing wire with a multi-level micro / nanoporous structure according to any one of claims 1-3, characterized in that, Includes the following steps: S01: Aluminum stranded wire surface pretreatment for cleaning; S02: Immerse the aluminum stranded wire in oxalic acid electrolyte and perform two anodizing treatments; control the temperature of the oxalic acid electrolyte at 10-20℃; The first anodizing process is set to a voltage-stabilized mode with a rapid voltage boost, a stabilized voltage of 55-60V, and an oxidation time of 10-20 minutes. The second anodizing process is set to a current-stabilized mode with a current density of 0.01~0.50 A / cm². 2 The oxidation treatment time is 10-20 minutes; Controlling Fe in the electrolyte 3+ The concentration is no more than 1 g / L.

5. The preparation method according to claim 4, characterized in that, Set the aluminum ion concentration in the oxalic acid electrolyte to 0.02-10 g / L; or, control the Fe concentration in the electrolyte. 3+ The concentration is 0.2-1 g / L.

6. The application of the anti-icing wire with a multi-level micro-nanoporous structure as described in any one of claims 1-3 in the preparation of long-lasting anti-condensation equipment.

Citation Information

Patent Citations

  • Preparation method of superamphiphobic SiO2 nano functional solution and application

    CN109181537A

  • A durable anti-icing wire for use in low-temperature and high-humidity environments and its preparation method

    CN116206801B

  • Method for preparing nano / submicron / micron multi-stage anode alumina template

    CN104294344A

  • Anti-icing overhead aluminum stranded wire and preparation method thereof

    CN110504062A